A Novel Scoring System in Predicting Prognosis After Adjuvant FOLFOX Chemotherapy in Gastric Cancer - Ge, Guochao; Li, Guangyao; Zhang, Zhengjun; Zhu, Yong; Wang, Wentao; Ren, Lei; Li, Ziqiang; Teng, Mujian (Cancer biotherapy & radiopharmaceuticals, 2023)
To evaluate the impact of neutrophil-to-lymphocyte ratio (NLR) and preoperative prognostic nutritional index (PNI) on prognosis of gastric cancer (GC) after adjuvant FOLFOX chemotherapy. Data on 749 GC patients who received operation after by adjuvant FOLFOX chemotherapy between January 2013 and December 2015 were enrolled in this study, retrospectively. Receiver-operating characteristic curve analysis was employed to assess optimal cutoff thresholds for PNI and NLR. The GC subjects having a low PNI (<52.8) and high NLR (>1.79) received a score of 2. Any variable that met these standards was scored as 1. If none of the two variables met these standards of the patient was assigned a score of 0. Correlation between PNI-NLR score and GC stage was also evaluated. The mean overall survival (OS) and 5-year OS rate for subjects with PNI-NLR = 2 was lower than those of subjects with PNI-NLR = 1, or 0 (40.9% vs. 52.1%, 76.4% [46.0 vs. 61.0], 68.0 months, ≤ 0.001). In multivariate analyses, the PNI-NLR score ( ≤ 0.001) and WHO grade ( ≤ 0.001) showed potential to independently influence OS. High PNI-NLR scores can independently affect worse prognosis of GC. Thus, it can be utilized to differentiate low risk from high risk subjects.